PENGARUH MODEL PEMBINAAN GURU DALAM MENINGKATKAN KINERJA GURU SMK NEGERI 4 BOJONEGORO - jurnalmap map; Mohamad Iswanto; Indra Prasetyo (MAP (Jurnal Manajemen dan Administrasi Publik), 2019)
ABSTRACT This study aims to determine and describe the coaching model teacher in SMK Negeri 4 Bojonegoro. As well as to identify and describe the role model of development in improving teacher performance SMK Negeri 4 Bojonegoro. The focus of research is further elaborated in several sub-focus can be formulated as follows: model coaching teacher in SMK Negeri 4 Bojonegoro. The object of this study is a model of teacher training and teacher performance. This study use qualitative data analisis, and the result of the study explained that the teacher coaching model SMK Negeri 4 Bojonegoro through the development of discipline, motivation, rewards, training, and supervision. The coaching model proven to improve the performance of teachers. The influence of coaching a teacher at SMK Negeri 4 Bojonegoro among others: the process of teacherÔÇÖs work will be better, optimaze working hours, ensuring that teachers are properly trained and can able toperform their jobs well, their handling and working arrangements are more mature, teachers job in quantitave result more satisfying, qualitative work better teacher. Keywords: coaching teacher model, teacher performance